DianaShawl / Nur Afiqah Ahmad … [et al.] - Ahmad, Nur Afiqah; Abdul Malek, Nurfarahanis; Abdul Hamid, Muhammad Hazim; Fadzlan, Nur Rabiatul Rahah; Mohd Lutpi Taufik, Nur Liyana (2022)
DianaShawl Enterprise, located in Malaysia, is a leading retail store scarf brand. DianaShawl is a Malaysian product brand that has attracted the eye of many Malaysians, especially women. We have provided some information on DianaShawl in this study, including company information, Business Management Canvas (BMC) analysis, findings, and discussion. The company information including the company's background, organization structures, products offered, business and marketing, operational strategy, and financial achievements. Nine BMC elements were used to develop and describe the company analysis. The company's findings include the company's challenges, while the recommendations focus on how the company solves challenges.